The Influence of Kahoot Media On Learning Outcomes Students In Learning Mathematics Fraction Material for Grade V - Redina Wila Wardana Rumahorbo; Hetdy Sitio; Jon Roi Tua Purba (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to determine the effect of Kahoot media on student learning outcomes in fraction mathematics learning for grade V of SD Negeri 091263 Karang Sari, Academic Year 2025/2026. This study uses a quantitative approach with a pre-experimental design and a One Group Pretest-Posttest Design. The sample in this study were all grade V students of SD Negeri 091263 Karang Sari, totaling 23 people. The data collection technique used tests in the form of pretest and posttest in the form of multiple choices of 25 questions. The results showed that the average student pretest score was 40.39 with an incomplete category, while the average posttest score was 84.69 with a complete category, which resulted in an increase in student learning outcomes. In addition, an N-Gain value of 0.72 was obtained with a high category, which indicated an increase in student learning outcomes. Based on the normality test using Shapiro-Wilk, a pretest significance value of 0.580 and a posttest significance value of 0.376 were obtained, so the data were normally distributed. Furthermore, the results of the paired sample t-test showed a significance value of 0.000 < 0.05, which means there is a significant difference between the pretest and posttest results. Thus, it can be concluded that the use of Kahoot learning media has a significant effect on improving student learning outcomes in mathematics learning on fractions in grade V of SD Negeri 091263 Karang Sari